GEREJA SEBAGAI UMAT TEBUSAN ALLAH YANG BERDAMPAK BAGI KOMUNITAS - Sitanggang, Tahan (JURNAL IMPARTA, 2024)
This study aims to understand the church as God's redeemed people who have an impact on the community. The church that has been redeemed by Jesus Christ must have a life that grows both in faith and in the practice of that faith. Pentecostals live the stages of Christianity called the Fivefold Gospel. The Christian life of Pentecostals must have an impact that is manifested in a practice of community life. The method used is qualitative descriptive. The results of this study explain. God's redeemed people must understand and also live in the Fivefold Gospel. The characteristics of the redeemed church must be an implementation of the church's task, namely preparing people who are worthy of God. Pentecostals must have an impact on the community in which they live (living in a community).